Protective effect of nano-extract of Lepidium meyenii on some func-tional parameters and epididymal tissue in male albino rats treated with the Oxymetholone - Alrushdy, Maryam Ahmed Ali; Obeid, Ashwaq Kadhem (Journal of Kerbala for Agricultural Sciences, 2024)
Due to the widespread use of the Oxymetholone and its widespread health problems, it was necessary to search for an alternative medicine treatment that reduces the harm of the Oxymetholone. Objectives from this study is determine the protective effect of the nano-extract of the Lepidium meyenii on the damage caused by the Oxymetholone in male rats. the experimental animals (28) were randomly divided into four groups, with 7 animals for each group The duration of the experiment was 55 days. The animal dosed daily, as follows: control group (G1): The animals were dosed with normal saline,Positive control group (G2): animals dosed orally with Oxymetholone (5 mg/kg B.w.),Group three (G3): Animals were dosed orally with the nano-extract of Lepidium meyenii ( 100 mg/kg B.w.),Group four (G4): It included animals dosed orally with the nano-extract of Lepidium meyenii (100 mg/kg B.w.) four hours before oral dosing with the Oxymetholone ( 5 mg/kg B.w.). The level of (GSH, SOD and number of sperm in epididymal tail) decreased in the Oxymetholone group and rose and was within the normal level in G3, G4.The histological sections of the epididymal in G2 It was noted that there were interstitial spaces between the epididymal tubules, and few sperm in the tubule cavities. With a lack of smooth muscle surrounding the tubules.Also showed in G3 and G4 the normal structure of the epididymis appears with regular epididymal tubules, an increase in the number of sperm in the lumen of the epididymis and the presence of connective tissue between the tubules. Maca root nano-extract has been shown to be effective in inhibiting oxymetholone-induced damage to oxidative stress and epididymal tissue in male rats.